2006
DOI: 10.1097/01.mjt.0000178338.43545.3a
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effects of Fentanyl in the Feline Pulmonary Vascular Bed

Abstract: The objective of this study was to test the hypothesis that fentanyl induces a depressor response in the pulmonary vascular bed of the cat and to identify the receptors involved in the mediation or modulation of these effects. The authors conducted a prospective vehicle-controlled study at a university research laboratory using intact chest preparation in adult mongrel cats. In separate experiments, the effects of diphenhydramine (histamine receptor blocker), glibenclamide (ATP-sensitive K+ channel blocker), L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Opioids including fentanyl and its derivatives can promote the pulmonary release of histamine (Kaye et al , 2006a; Kaye et al , 2006b), which was reported to sensitize PCFs (Lee & Morton, 1993; Undem & Weinreich, 1993). Furthermore, inhaling histamine causes a rapid breathing by activating histamine H 1 or H 2 receptors of pulmonary sensory fibers in baboons (Yeates & Hameister, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Opioids including fentanyl and its derivatives can promote the pulmonary release of histamine (Kaye et al , 2006a; Kaye et al , 2006b), which was reported to sensitize PCFs (Lee & Morton, 1993; Undem & Weinreich, 1993). Furthermore, inhaling histamine causes a rapid breathing by activating histamine H 1 or H 2 receptors of pulmonary sensory fibers in baboons (Yeates & Hameister, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a vasodilatory effect on pulmonary vascular pressures in animals has been demonstrated. 1 Opioids have historically been used to treat anxiety and pain, which are often an integral part of the dyspnea cycle; the positive effects on these symptoms have been extensively reviewed. 2 Proof-of-concept for the use of opioids in dyspnea was confirmed in a recent report of measured endogenous opioids during dyspnea.…”
Section: Opioid Efficacymentioning
confidence: 99%
“…Part one of this two-part series on dyspnea for the palliative care professional describes the burden and measurement of dyspnea. 1 Because of its complex biopsychosocial etiology and manifestations, dyspnea presents a particularly challenging symptom to manage-yet it is one which, nonetheless, requires an evidence-based symptom management approach. An armamentarium of both restorative and global therapies is available to address the modifiable and fixed components to dyspnea.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of sensory neuropeptide release by OFQ/N leads to hyperaemia in acutely inflamed rat knees (1303). Remifentanil, sufentanil and fentanyl each induced a dose-dependent vasodepressor response in the cat pulmonary vascular bed that was attenuated by naloxone and diphenhydramine, but not glibenclamide (562,564,565). In contrast, meperidine induced a dose-dependent vasodilator response in the cat pulmonary vascular bed that was attenuated by naloxone and diphenhydramine, but not glibenclamide (563).…”
Section: C Blood Pressurementioning
confidence: 99%